Hypoxia modulation vs. chemotherapy and tumor shrinkage on early response assessment in diffuse large B-cell lymphoma - Naibaho, Ridho M.; Pangarsa, Eko; Rizky, Daniel; Kurniawan, Sigit P.; Istiadi, Hermawan; Puspasari, Dik; Santoso, Gunawan; Santosa, Damai; Setiawan, Budi; Suharti, Catharina (Archive of Oncology, 2024)
Background: Rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) chemotherapy remains the standard of first-line treatment for diffuse large B-cell lymphoma (DLBCL). Up to 40% of DLBCL is characterized by relapse and refractory after treatment. Preliminary study reported Hypoxia-inducible factor-1  (HIF-1 ) overexpression in 88.5% of DLBCL tumors in the Dr. Kariadi Hospital. Moreover, the role of hypoxia and HIF-1  has previously never been explored in DLBCL. Objectives: To evaluate the effect of hypoxia modulation to increased chemotherapeutic response in DLBCL.Methods: Single blind randomized control study was performed, with pre-test and post-test control group design. Research sampling consisted of DLBCL patients. The inclusion criteria include newly diagnosed DLBCL with HIF-1  overexpression and randomized to receive hypoxia modulation consisting of carbogen inhalation and nicotinamide administration, before R-CHOP chemotherapy. The tissue biopsy, histopathology and immunohistochemical studies were done. Chemotherapeutic responses were evaluated after 10-14 days following the first cycle of R-CHOP chemotherapy. Results: Out of twenty-six DLBCL participants with HIF-1  overexpression, there were 20 participants who completed the research protocol: 10 participants each in the intervention and control group. Demographic, clinicopathological, laboratory and disease characteristics were not statistically different between the two research groups (p>0.05). Baseline tumor volume to be evaluated was also considered equal (172.3 cm3 vs. 152.8 cm3, p=0.597). Following the carbogen inhalation and nicotinamide administration, serum HIF-1  and lactate reduction can be observed. There was also a significant tumor volume shrinkage in both the intervention and control (mean –85.7 cm3 vs. –118.27 cm3) group, though the reduction was not statistically different (Delta 58.85% vs. 65.63%, p=0.474).  Conclusion: The addition of hypoxia modulation to R-CHOP chemotherapy for DLBCL has shown beneficial effects on both serum HIF-1  and lactate concentration. However, the benefits did not correlate to increase a better tumor response compared to the control group.
Keywords: Hypoxia modulation; lactate; tumor volume; diffuse large B-cell lymphoma